2023
DOI: 10.3390/ani13091510
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Full-Fat Silkworm-Based Diets for Laying Quails: Performance and Egg Physical Quality

Abstract: The present research was conducted to determine the optimal inclusion level of full-fat silkworm chrysalis meal (SWM) into laying quails’ diets, focusing on performance traits and egg physical quality. A total of 240 31-day-old female Japanese quails were randomly assigned to four dietary groups (12 replicates/treatment; 5 quails/replicate); quails were initially fed a standard commercial diet for pullets until 63 days of age. When oviposition started, the experimental groups received the following diets: a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Coherently to previous research on eggs obtained from quails fed with different insect sources ( Dalle Zotte et al, 2019 ; Singh et al, 2023 ), also in the present trial no particular effects linked to the dietary treatment on eggs’ shelf-life were observed. The pH values of quail eggs (average: 8.66) at d 0 of shelf-life are typical for this species ( Dalle Zotte et al, 2019 ) and are indicative of freshness.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Coherently to previous research on eggs obtained from quails fed with different insect sources ( Dalle Zotte et al, 2019 ; Singh et al, 2023 ), also in the present trial no particular effects linked to the dietary treatment on eggs’ shelf-life were observed. The pH values of quail eggs (average: 8.66) at d 0 of shelf-life are typical for this species ( Dalle Zotte et al, 2019 ) and are indicative of freshness.…”
Section: Discussionsupporting
confidence: 85%
“…The laying quails were divided into 2 experimental groups: the first group received the Control diet in mash form, whereas the second group received the Control diet, daily supplemented with live TM larvae (TM10: 10% of the expected daily feed intake, which was calculated based on data from previous trials ( Dalle Zotte et al, 2019 ; Singh et al, 2023 ) on laying quails of the same age). The 8-wk-old live TM larvae were provided by INEF - Insect Novel Ecologic Food (Via Fossetta, 23, 35017 Piombino Dese, Padova, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Sampling was performed on Japanese quails subjected to parasitological examinations as part of a study designed to evaluate the effects of different diets on laying quail performance (the study was approved by the Ethical Committee of the University of Padova, Protocol n. EC2018/87), whose farming specifications can be found in the study by Singh et al (2023) . From March to May 2021, 12 pools contents both from caeca and cloaca were separately collected from a total of 240 laying quails, stored at +4°C and subjected to parasitological analyses within 24 h.…”
Section: Methodsmentioning
confidence: 99%